From the plant to the pot - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Tea by Denis Bonheure 102pp 1990 ISBN 0 333 54450 1 Tropical Agriculturalist series published by Macmillan Publishers Ltd, 4 Little Essex Street, London WC2, UK Available from CTA